Designing environments for people with dementia : a systematic literature review - Bowes, Alison; Dawson, Alison (Emerald points., 2019)
This review systematically explores and assesses the quality of the evidence base for effective and supportive design of living environments for people living with Dementia. Dementia is a major challenge for all countries, as the population with the condition is growing rapidly. Societies desperately need to identify measures which mean that they can continue to thrive with a large population of people who are cognitively impaired. Medical treatments are poor, and there is little indication of better medications appearing in the coming decades. There is urgent need for non-medical advances which can address the challenge including ensuring environments are conducive to living better with Dementia. Whilst there is a lot of activity in this area of Dementia friendly design, the evidence base remains poorly synthesized and weak.This book pulls evidence together to provide a solid reference point from which further research and further developments in the field of Dementia care and support can proceed.The ebook edition of this title is Open Access and is freely available to read online.